2008
DOI: 10.1017/s0007114507844138
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in Sri Lankans living in Sri Lanka and Norway

Abstract: Vitamin D deficiency is common in non-Western immigrant groups living in Western countries. A comparison of vitamin D status in individualswho have emigrated and individuals who remain in their country of origin is needed in order to provide information about the effect of moving to northern latitudes. A total of 196 participants aged 30-60 years in a cross-sectional population-based study in Kandy, Sri Lanka (latitude 78 north) and 242 Sri Lankans aged 31-60 years participating in a cross-sectional population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 15 publications
(17 reference statements)
3
30
2
Order By: Relevance
“…Other researchers documented that the prevalence of serum 25(OH)D levels of < 25 nmol/l was 9.3 times higher in Sri Lankans living in Norway compared with those in Sri Lanka [21]. Therefore, this data suggest that migration to northern latitudes, where there is lesser sun light, confers increased risk of developing vitamin D deficiency.…”
Section: Introductionmentioning
confidence: 69%
“…Other researchers documented that the prevalence of serum 25(OH)D levels of < 25 nmol/l was 9.3 times higher in Sri Lankans living in Norway compared with those in Sri Lanka [21]. Therefore, this data suggest that migration to northern latitudes, where there is lesser sun light, confers increased risk of developing vitamin D deficiency.…”
Section: Introductionmentioning
confidence: 69%
“…Ten studies of vitamin D deficiency among the general population were identified, two from Denmark (65, 66), seven from Norway (57, 63, 68, 7578), and one from Sweden (58). …”
Section: Resultsmentioning
confidence: 99%
“…A one centimeter difference in height was associated with 0.004 g/cm 2 Regression model was fitted with PTH as the dependent variable and vitamin D as the independent variable to assess the relationship of these two variables (Figure 1). Using the regression equation (intercept = 73.08 and [12] estimated 25-vitD levels of Sri Lankan ethnic Tamils from the central part of the country and compared it with a similar ethnic group in Norway. In their analysis among 30 -60-year-old community-dwelling Sri Lankan women, the mean 25-vitD level was 47.4 ± 15.8 nmol/L.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge on vitamin D status among Sri Lankan is limited [12]. There were no studies done on Sri Lankan men's vitamin D levels.…”
Section: Introductionmentioning
confidence: 99%